Комплесна оцінка й аналіз формування стратегії розвитку кадрового потенціалу ВНЗ - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2014)
A theoretical and methodological approach to the analysis of human resources universities based on evaluation of the teaching staff (teaching, research and social work), which makes it possible to estimate the complex as personal as teachers and their performance.